Two type I topoisomerases maintain DNA topology in human mitochondria. Issue 19 (10th October 2022) - Menger, Katja E; Chapman, James; Díaz-Maldonado, Héctor; Khazeem, Mushtaq M; Deen, Dasha; Erdinc, Direnis; Casement, John W; Di Leo, Valeria; Pyle, Angela; Rodríguez-Luis, Alejandro; Cowell, Ian G; Falkenberg, Maria; et al.
Abstract: Genetic processes require the activity of multiple topoisomerases, essential enzymes that remove topological tension and intermolecular linkages in DNA. We have investigated the subcellular localisation and activity of the six human topoisomerases with a view to understanding the topological maintenance of human mitochondrial DNA. Our results indicate that mitochondria contain two topoisomerases, TOP1MT and TOP3A. Using molecular, genomic and biochemical methods we find that both proteins contribute to mtDNA replication, in addition to the decatenation role of TOP3A, and that TOP1MT is stimulated by mtSSB. Loss of TOP3A or TOP1MT also dysregulates mitochondrial gene expression, and both proteins promote transcription elongation in vitro . We find no evidence for TOP2 localisation to mitochondria, and TOP2B knockout does not affect mtDNA maintenance or expression. Our results suggest a division of labour between TOP3A and TOP1MT in mtDNA topology control that is required for the proper maintenance and expression of human mtDNA.